Ethnobotanical study of the Chơ Ro minority in Dong Nai Culture and Nature Reserve, Vietnam - Nguyen, Xuan-Minh-Ai; Nguyen, Thi-Mai-Anh (Ethnobotany Research and Applications, 2024)
Background: The Chơ Ro ethnic community in Dong Nai Culture and Nature Reserve has diverse traditional knowledge of plants, but it has disappeared at an alarming rate for various reasons. Methods: An ethnobotanical study was conducted from March to June 2022 in Ly Lich 1 hamlet, Phu Ly commune, through semi-structured interviews and field surveys involving seven key informants. The aim was to compile an inventory of useful plants utilized by the local community. Additionally, focus groups were employed to identify priority species based on community perception. Results: A total of 118 taxa, belonging to 57 plant families, were identified as being utilized by the community across eight main categories. Among these, food comprised the largest group, accounting for 66.0% of total use reports, with various plant parts being utilized. Using three techniques of the Participatory Rural Appraisal (PRA) approach, including free-listing, direct ranking, and pair-wise ranking, it was determined that Gnetum gnemon L. and Lasia spinosa (L.) Thwaites were the most important species for the Chơ Ro people. Consequently, distribution maps for these species within the study site were created based on field surveys. Conclusions: The study's findings contribute significantly to the preservation of Chơ Ro's indigenous knowledge and provide essential data for biodiversity conservation and the sustainable development of local resources. Keywords: Ethnobotany; Chơ Ro; Indigenous knowledge; Priority species